Tantangan dan Inovasi Pendidikan Indonesia: Evaluasi, Solusi, Ekspektasi - Sinuraya, Ananda Mardianus; Asbari, Masduki; Angin, Sharon Hillary Br Perangin (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to encourage improvement in order to have better abilities, awareness, skills and quality of life in general. This study uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Satu Youtube channel Percent entitled "Indonesian Education Notes; Evaluation, Solutions, Expectations" | Satu Insight #50. The results of this study explain building a solid foundation and knowledge, analytical and critical skills. This research begins with identifying results related to study objectives to develop or revise existing policies, to achieve these objectives more efficiently.